PRACTICES OF REPRESENTATION OF SPACE AS AN OBJECT OF CULTURAL STUDIES - Fanahei, Rostyslav (Ukrainian Cultural Studies, 2023)
The article is aimed at substantiating the potential of "spatial expansion" of both problematics and optics of cultural studies in their deepening and systematization by the conceptualization of practices of representing space. Late modern cultural studies in general actualize questions not about means of mediation — representations as objects, such as artifacts or mentifacts, and about the very methods of mediation — representations as processes — which is what practices are. At the same time, the "expansion" of these studies, outlined in the article, justifies such adjustment and allows to fully reveal under the temporal production of meanings the corporeal-spatial production of presence, as the basis of human experience of the world, and spatial organization as the main instrument of visual and tactile power relations, which are exercised through discourses, or directly. Moreover, it enables the systematization of a heterogeneous ensemble of practices of representing space in their historical dynamics. A. Lefebvre conceptualized this multiplicity of practices in the constant interaction of "representations of space" and "spaces of representation", which should be considered as fillings of the Foucault dispositive system between catching and the environment. Representations of space as a way of practice reflect the rationalized and visualized production of meanings in terms of both reflection and construction. Spaces of representation reflect the symbolic-corporeal dimension of representation as an imprint of presence, thanks to which we transform the world with our projection, and the presence of the world is given to us for use. On the basis of the outlined system, it is possible to single out a number of practices that are quite generalized and that exert, perhaps, a greater influence on the historical dynamics of the entire heterogeneous ensemble. This series of practices of "spatial issues" justifies the expediency of "spatial optics" at the subject level